SFRP2 mediates Epstein-Barr virus and bladder cancer risk: a Mendelian randomization study and colocalization analysis - Jian Li; Bing Yang; Lei Guo; Wenqi Huang; Qiong Hu; Hongting Yan; Changpu Du; Rong Tan; Dongxin Tang (Scientific Reports)
Abstract Studies suggest a possible association between Epstein-Barr virus (EBV) infection and bladder cancer (BCa) risk, though this remains unclear. Secreted frizzled-related protein (sFRP) is also linked to BCa, with some DNA viruses potentially regulating its expression. This study used Mendelian randomization (MR) and colocalization analysis to explore the causal relationship between EBV infection, BCa risk, and the mediating role of sFRP. We first performed a two-sample MR study to assess the causal relationship between 5 EBV-related antibodies (AEB-IgG, EA-D, EBNA-1, VCA-p18, ZEBRA) and BCa using the Finnish Consortium’s R11 dataset, validated with R10. Reverse MR analysis followed. For significant results, multivariable MR (MVMR) was applied to adjust for confounding risk factors. A two-step MR explored the potential mediating role of 3 sFRPs (sFRP1, sFRP2, sFRP3) between positive exposures and BCa. Colocalization analysis were conducted for positive exposures, mediators, and BCa, with multiple sensitivity analyses confirming the robustness of the results. The two-sample Mendelian randomization study found that EBNA-1 (OR = 1.15, 95% CI: 1.01–1.30; p = 0.039) and VCA-p18 (OR = 1.36, 95% CI: 1.13–1.64; p = 0.001) may increase BCa risk, with only VCA-p18 (P_fdr = 0.006) showing a significant effect after False Discovery Rate (FDR) correction. The Finnish Consortium R10 replication study yielded similar results, and reverse MR analysis did not suggest reverse causality. After MVMR adjusted for relevant confounders, VCA-p18 (OR = 1.40, 95% CI: 1.13–1.74; p = 0.002) still significantly increased BCa risk. Two-step MR identified sFRP2 as a mediator, with VCA-p18 down-regulating sFRP2 expression to elevate BCa risk. Colocalization analysis suggested a shared causal variant (nearby gene HLA-DQA1) between VCA-p18 and BCa (PPH4 = 65.44%). Multiple sensitivity analyses confirmed the robustness of the results. Our study suggests that EBV infection (VCA-p18 antibody) may increase the risk of BCa by lowering sFRP2 levels. Additionally, EBNA-1 antibodies may also contribute to an elevated risk of BCa. We hope these findings will provide new insights for future research on the association between EBV and BCa.